Screening for Posttraumatic Stress Disorder among Somali ex-combatants: A validation study - Odenwald, Michael (BioMed Central, 2007)
BACKGROUND: In Somalia, a large number of active and former combatants are affected by psychological problems such as Posttraumatic Stress Disorder (PTSD). This disorder impairs their ability to re-integrate into civilian life. However, many screening instruments for Posttraumatic Stress Disorder used in post-conflict settings have limited validity. Here we report on development and validation of a screening tool for PTSD in Somali language with a sample of ex-combatants. METHODS: We adapted the Posttraumatic Diagnostic Scale (PDS) to reflect linguistic and cultural differences within the Somali community so that local interviewers could be trained to administer the scale. For validation purposes, a randomly selected group of 135 Somali ex-combatants was screened by trained local interviewers; 64 of them were then re-assessed by trained clinical psychologists using the Composite International Diagnostic Interview (CIDI) and the Self-Report Questionnaire (SRQ-20). RESULTS: The screening instrument showed good internal consistency (Cronbach's α = .86), convergent validity with the CIDI (sensitivity = .90; specificity = .90) as well as concurrent validity: positive cases showed higher SRQ-20 scores, higher prevalence of psychotic symptoms, and higher levels of intake of the local stimulant drug khat. Compared to a single cut-off score, the multi-criteria scoring, in keeping with the DSM-IV, produced more diagnostic specificity. CONCLUSION: The results provide evidence that our screening instrument is a reliable and valid method to detect PTSD among Somali ex-combatants. A future Disarmament, Demobilization and Reintegration Program in Somalia is recommended to screen for PTSD in order to identify ex-combatants with special psycho-social needs.